Evaluasi Efektivitas Sistem Autentikasi Dua Faktor (2FA) terhadap Kepercayaan Pengguna Aplikasi Digital dengan Pendekatan Statistik - Fadila Nur Syifa; Akbar Priyanto; Purwadi Purwadi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The rapid development of digital technology has led to an increasing demand for effective security systems to protect user information. One popular method is two-factor authentication (2FA), which adds another layer of protection beyond passwords. This study aims to assess the effectiveness of 2FA implementation in increasing user trust when accessing digital services. The method used in this study was a quantitative approach, collecting data through questionnaires administered to a group of respondents who use digital applications. The collected data were then analyzed using descriptive and inferential statistical techniques to explore the relationship between 2FA use and user trust levels. The study findings indicate that most respondents feel more secure and trust systems that use 2FA compared to those that only implement single-factor authentication. Furthermore, the statistical analysis indicates a positive correlation between 2FA implementation and increased user trust. Thus, it can be concluded that user views of 2FA are generally positive. This research is expected to serve as a reference for system developers in improving user security and convenience.